Creating water user associations for improved agricultural productivity in Tajikistan: opportunities and challenges - Balasubramanya, Soumya; Buisson, Marie-Charlotte; Aslamy, Sohrob; MacDonald, Katherine; Saikia, Panchali; Mitra, A. (2016)
After Tajikistan emerged an independent country, major land reforms took place. Large collective farms were broken up into smaller (dekhan) private farms. This created a vacuum, because there was no provision to manage competing needs of water among private farms. Water user associations were created with the efforts of the government, and several international donors, to manage distribution of water between private farms and to share in maintenance of smaller canals. In this paper we provide a brief description of the creation of water user associations, as well as their roles and responsibilities. We then describe the opportunities for increasing livelihoods, and contributing to increased agricultural productivity. Can these WUAs improve access to and distribution of water? Would better irrigations services increase cropping areas? Would yields of cotton improve? Can these be an improvement in crop diversity? We identify the key existing gaps in knowledge, that would provide an understanding of the impacts of these associations on wellbeing. We also describe some of the challenges that may limit the efficacy of these associations. Are these institutions likely to be able to cover their operational costs? Can these institutions serve well as cropping decisions change? Are these institutions likely to represent the needs of female farmers? We identify the key factors that need to be examined more closely, that provide an understating of the resilience of these associations. The answers to these questions would provide important information for policies to support and strengthen water user associations in Tajikistan.